2016
DOI: 10.1080/02699931.2016.1273200
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to individual differences in facial expression categorisation

Abstract: Individuals vary in perceptual accuracy when categorising facial expressions, yet it is unclear how these individual differences in non-clinical population are related to cognitive processing stages at facial information acquisition and interpretation. We tested 104 healthy adults in a facial expression categorisation task, and correlated their categorisation accuracy with face-viewing gaze allocation and personal traits assessed with Autism Quotient, anxiety inventory and Self-Monitoring Scale. The gaze alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 59 publications
4
24
0
Order By: Relevance
“…In addition, although the images used in our study were extracted from the same database used in other studies (12,15,16), and the images were randomly selected, the emotions shown in the images may have been more difficult to recognize than in the images used in other studies. The visual behavior of the healthy participants was also consistent with existing reports, showing that eyes, noses, and mouths are the most relevant facial structures used in identifying facial expressions (12)(13)(14)(15)59). The hierarchical distribution of attention to the eyes, followed by the nose and the mouth, is also supported in most of the existing literature (11,15,16).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, although the images used in our study were extracted from the same database used in other studies (12,15,16), and the images were randomly selected, the emotions shown in the images may have been more difficult to recognize than in the images used in other studies. The visual behavior of the healthy participants was also consistent with existing reports, showing that eyes, noses, and mouths are the most relevant facial structures used in identifying facial expressions (12)(13)(14)(15)59). The hierarchical distribution of attention to the eyes, followed by the nose and the mouth, is also supported in most of the existing literature (11,15,16).…”
Section: Discussionsupporting
confidence: 86%
“…Gaze behavior was defined in terms of the number of fixations-also known as fixation count-and the total time spent-also known as total fixation duration-on the eyes, nose, and mouth, which, as mentioned above, have been identified as being the most representative areas involved in a visual scan of the face (11,12,14,15,59). These areas were manually defined for each visual stimulus image, in accordance with previous studies (11,12,15,59). The averaged pupil diameter variation was also extracted, as in previous studies (18,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…The Ethical Committee in School of Psychology, University of Lincoln approved this study. Written The general experimental setup and testing procedure has been described in our previous publications (e.g., Guo & Shaw, 2015;Green & Guo, 2017). Briefly, digitized greyscale face images in full frontal view were presented through a ViSaGe graphics system (Cambridge Research Systems, UK) and displayed on a non-interlaced gamma-corrected colour monitor (30 cd/m 2 background luminance, 100 Hz frame rate, Mitsubishi Diamond Pro 2070SB) with the resolution of 1024 × 768 pixels.…”
Section: Methodsmentioning
confidence: 99%
“…When facial configurations are ambiguous or subtle, adults (and children) shift their attention between the eyes and other facial features that may provide additional diagnostic information [18]. For instance, to make inferences about whether wide eyes indicate "fear" or "surprise," adults attend to both the eyes and the mouth [19,20]. Adults also tend to fixate on specific facial features that characterize specific emotion stereotypes, such as the mouth for happiness and the nose for disgust [8][9][10]21].…”
Section: Introductionmentioning
confidence: 99%